Model of Islamic Civilization in Indonesia - Tenny Sudjatnika; Rizkia Shafarini (Islamic Research, 2022)
Islam is part of the source of civilization for its adherents. It is adjusted to the term civilization itself, which has the meaning of the product of activities in human life, both in the economic, social, political, educational fields, and so on. Thus, in this case, Islam as a religion, in its holy writings, also provides a clue about the things needed in human life, although not in clear language. Enforcing the implementation of Arabic Islamic Sharia into society such as in Indonesia will form a feeling of alienation in religion. For example, in the case of wearing the hijab for Muslim women. Arab or Middle Eastern dress models and hijabs have black color. If these models are used in the Muslim community in Indonesia, the users will look different and seem strange in the community itself. Therefore, a wise attitude is needed in the implementation of religious teaching to adjust according to the existing local or local culture.